Patient-Centered Identification of Meaningful Regulatory Endpoints for Medical Devices to Treat Parkinson's Disease. Issue 1 (June 2021) - Benz, Heather L.; Caldwell, Brittany; Ruiz, John P.; Saha, Anindita; Ho, Martin; Christopher, Stephanie; Bardot, Dawn; Sheehan, Margaret; Donnelly, Anne; McLaughlin, Lauren; Mange, Brennan; Hauber, A. Brett; et al.
Introduction. A growing literature has developed on identifying outcomes that matter to patients. This study demonstrates an approach involving patient and regulatory perspectives to identify outcomes that are meaningful in the context of medical devices for Parkinson's disease (PD).Methods. A systematic process was used for specifying relevant regulatory endpoints by synthesizing inputs of various sources and stakeholders. First, a literature review was conducted to identify important benefits, risks, and other considerations for medical devices to treat PD; patient discussion groups ( n = 6) were conducted to refine the list of considerations, followed by a survey ( n = 29) to prioritize them; and patient and Food and Drug Administration (FDA) reviewers informed specification of the final endpoints. Two FDA clinicians gave clinical and regulatory perspectives at each step.Results. Movement symptoms were ranked as most important (ranked 1 or 2 by 72% of participants) and psychological and cognitive symptoms as the next most important (ranked 1 or 2 by 52% of participants). Within movement symptoms, falls, impaired movement, bradykinesia, resting tremor, stiffness, and rigidity were ranked highly. Overall, nine attributes were identified and prioritized as patient-centric for use in clinical trial design and quantitative patient preference studies. These attributes were benefits and risks related to therapeutics for PD as well as other considerations, including time until a medical device is available for patient use.Discussion. This prospective approach identified meaningful and relevant benefits, risks, and other considerations that may be used for clinical trial design and quantitative patient preference studies. Although PD was the focus of this study, the approach can be used to study patient perspectives about other disease or treatment areas.